Azur Like It - Holden, Wendy, 1965- (London Headline, 2003)
Kate, a journalist in a small northern town, dreams of a glamourous life in the South of France. There's little less glamourous than the Slackmucklethwaite Mercury and with a ruthless new boss, things get worse, until his handsome son Nat shows up and sweeps Kate off to the Cannes Film Festival.
Keywords: Women journalists -- France--Riviera -- Motion picture industry